Investigating the Role of Surface Roughness and Defects on EC Breakdown, as a Precursor to SEI Formation in Hard Carbon Sodium‐Ion Battery Anodes. Issue 43 (26th August 2022) - Olsson, Emilia; Cottom, Jonathon; Alptekin, Hande; Au, Heather; Crespo‐Ribadeneyra, Maria; Titirici, Maria‐Magdalena; Cai, Qiong
Abstract: Hard carbon (HC) anodes together with ethylene carbonate (EC)‐based electrolytes have shown significant promise for high‐performing sodium‐ion batteries. However, questions remain in relation to the initial contact between the carbon surface and the EC molecules. The surface of the HC anode is complex and can contain both flat pristine carbon surfaces, curvature, nanoscale roughness, and heteroatom defects. Combining density functional theory and experiments, the effect of different carbon surface motifs and defects on EC adsorption are probed, concluding that EC itself does not block any sodium storage sites. Nevertheless, the EC breakdown products do show strong adsorption on the same carbon surface motifs, indicating that the carbon surface defect sites can become occupied by the EC breakdown products, leading to competition between the sodium and EC fragments. Furthermore, it is shown that the EC fragments can react with a carbon vacancy or oxygen defect to give rise to CO2 formation and further oxygen functionalization of the carbon surface. Experimental characterization of two HC materials with different microstructure and defect concentrations further confirms that a significant concentration of oxygen‐containing defects and disorder leads to a thicker solid electrolyte interphase, highlighting the significant effect of atomic‐scale carbon structure on EC interaction. Abstract : In this work, the binding and breakdown of ethylene carbonate (EC) on hard carbon (HC) are explored. Exploring how the surface termination, roughness, and defects influence the initial EC–HC interaction and facilitate breakdown.